The Ameliorative Effect of JNK Inhibitor D-JNKI-1 on Neomycin-Induced Apoptosis in HEI-OC1 Cells - Zhao, Junling; Liu, Hao; Huang, Zhiwei; Yang, Ruiming; Gong, Liang (Frontiers in Molecular Neuroscience, 2022)
Aminoglycosides can cause ototoxicity and lead to hair cell damage. Neomycin-induced ototoxicity is related to increased production of reactive oxygen species (ROS) and triggering hair cell apoptosis. The JNK pathway plays an essential role during hair cell damage. The present study was designed to investigate an inhibitor of JNK, D-JNKI-1 (AM-111/brimapitide) in neomycin-induced HEI-OC1 cell apoptosis. The results demonstrate that neomycin increased intracellular ROS accumulation, which induces apoptosis. D-JNKI-1 decreased neomycin-induced ROS generation, reduced caspase-8 and cleavage of caspase-3 expression, sustained JNK activation and AMPK and p38 phosphorylation, down-regulated Bax, and up-regulated Bcl-2. Together, D-JNKI-1 plays an essential role in protecting against neomycin-induced HEI-OC1 cell apoptosis by suppressing ROS generation, which inhibited JNK activation, AMPK and p38 phosphorylation to ameliorate JNK-mediated HEI-OC1 cell apoptosis.